2011
DOI: 10.1091/mbc.e11-02-0155
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar H+-ATPase subunits Voa1 and Voa2 cooperatively regulate secretory vesicle acidification, transmitter uptake, and storage

Abstract: Voa1 and Voa2 cooperatively regulate the acidification and transmitter uptake/storage of dense-core vesicles, although they might not be as critical for exocytosis as recently proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 74 publications
2
41
0
Order By: Relevance
“…In our current study, we could show that lysosomes purified from PS1KO cells contained markedly lowered levels of V0a1 subunit, which was associated with impaired vATPase assembly on lysosomes and commensurate reductions of lysosomal proton pumping activity. Using siRNA gene knockdown, we further demonstrated that lysosomal acidification and lysosomal enzyme activation require the vATPase V0a1 subunit, in agreement with other findings that V0a1 subunit is critical for vesicular acidification (Raines et al, 2013; Saw et al, 2011). Notably, V0a1 has a long half-life on lysosomes, requiring substantial duration of siRNA exposure (96hrs) to lower lysosomal levels of the subunit sufficiently to alter acidification, which is 48hrs longer than the interval used in the Coen et al study where a pH change could not be detected upon siRNA treatment (Coen et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In our current study, we could show that lysosomes purified from PS1KO cells contained markedly lowered levels of V0a1 subunit, which was associated with impaired vATPase assembly on lysosomes and commensurate reductions of lysosomal proton pumping activity. Using siRNA gene knockdown, we further demonstrated that lysosomal acidification and lysosomal enzyme activation require the vATPase V0a1 subunit, in agreement with other findings that V0a1 subunit is critical for vesicular acidification (Raines et al, 2013; Saw et al, 2011). Notably, V0a1 has a long half-life on lysosomes, requiring substantial duration of siRNA exposure (96hrs) to lower lysosomal levels of the subunit sufficiently to alter acidification, which is 48hrs longer than the interval used in the Coen et al study where a pH change could not be detected upon siRNA treatment (Coen et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…A recent report demonstrated that V0a1 plays an important role in regulating neurotransmitter uptake, storage, and release by exocytic vesicles in neurosecretory PC12 cells (Saw et al, 2011). Here, we found that cleaved caspase 3 was up-regulated and V0a1 was reduced in the NT-3 h group after CA compared to the HT-3 h group.…”
Section: Discussionsupporting
confidence: 50%
“…There are 4 isoforms of the V0a subunit, and each isoform is thought to have a role in the trafficking of the V-ATPase to different organelles in various types of cells as well as in the regulatory uncoupling of V0 and V1 and in membrane fusion [9,10,41,42]. The a1V isoform is involved in acidification of endomembrane organelles, especially in the microglia and other secretory cells of the brain and is prevalent in secretory granules of neurons or other cells in the brain; it has a role in the exocytosis of neurotransmitters in those granules [36,43]. The a2V isoform is found in vesicles in the thymus, decidua, hematopoietic cells, dividing cells, epididymal clear cells [11,34,44,45], and on the plasma membranes of macrophages [18,20].…”
Section: Discussionmentioning
confidence: 99%